Innovations and technological comebacks - Foucart, Renaud; Wan, Cheng; Wang, Shidong (Elsevier, 2018)
Motivated by the comeback of the vinyl, we explore the idea that the success of a third-generation technology (digital music) can have adverse effects on the second generation (CD) but positive effects on the first one (vinyl). This phenomenon arises in a market if the process of innovation is not transitive. In particular, we identify a condition such that the second generation completely substitutes the first one, the third generation completely substitutes the second one, but the first and the third generations have enough complementarities to coexist. Beyond the case of music industry, our model has implications on product positioning and product design.